CULTURAL HERITAGE AND THE FUTURE - Holtorf, Cornelius, 1968-; Högberg, Anders ([Place of publication not identified], ROUTLEDGE, 2017)
Cultural Heritage and the Future brings together an international group of scholars and experts to consider the relationship between cultural heritage and the future. Drawing on case studies from around the world, the contributing authors insist that cultural heritage and the future are intimately linked and that the development of futures thinking should be a priority for academics, students and those working in the wider professional heritage sector.Until recently, thefuture has never attracted substantial research and debate within heritage studies and heritage management, and this book addresses this gap by offering a balance of theoretical and empirical content that will stimulate multidisciplinary debate in the burgeoning field of critical heritage studies. Cultural Heritage and the Future questions the role of heritage in future making and will be of great relevance to academics and students working in the fields of museum and heritage studies, archaeology, anthropology, architecture, conservation studies, sociology, history and geography. Those working in the heritage professions will also find much to interest them within the pages of this book.
OCLC-licensed vendor bibliographic record.
Keywords: Cultural property -- Protection -- Case studies; Cultural property -- Protection -- Planning; Historic preservation -- Case studies; Historic preservation -- Planning; Cultural policy -- Case studies; SOCIAL SCIENCE / Archaeology